1997
DOI: 10.1007/s001470050074
|View full text |Cite
|
Sign up to set email alerts
|

Cold storage sensitizes hepatocytes to oxidative stress injury

Abstract: Liver cold storage leads to oxygen free radical production and reperfusion injury. Antioxidants are effective in suppression reperfusion injury in rat livers when used in the reperfusion medium. However, in clinical liver transplantation their effectiveness is not clear, which may be due to the way they are used (in the recipient). In this study we compare the effectiveness of antioxidants when used in the reperfusion medium versus the cold storage solution in isolated hepatocytes and the isolated perfused liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Fuller et al observed an increased susceptibility of kidney homogenates to lipid peroxidation (assessed after incubation of the homogenate for 90 min at 37°C under aerobic conditions) after cold storage of the kidneys, which was preventable using deferoxamine (47). Similarly, Vreugdenhil et al found an increased susceptibility of cold-stored hepatocytes and rat livers toward oxidative stress induced by t-butyl hydroperoxide, which was decreased by deferoxamine (48). These findings might well be due to the alterations discussed here.…”
Section: Similarly In Liver Endothelial Cells Omentioning
confidence: 59%
“…Fuller et al observed an increased susceptibility of kidney homogenates to lipid peroxidation (assessed after incubation of the homogenate for 90 min at 37°C under aerobic conditions) after cold storage of the kidneys, which was preventable using deferoxamine (47). Similarly, Vreugdenhil et al found an increased susceptibility of cold-stored hepatocytes and rat livers toward oxidative stress induced by t-butyl hydroperoxide, which was decreased by deferoxamine (48). These findings might well be due to the alterations discussed here.…”
Section: Similarly In Liver Endothelial Cells Omentioning
confidence: 59%
“…The amount of cellular free chelatable iron in isolated rat hepatocytes increased after 30 min of cold preservation and stayed at this level for 6 h (13). Cold preservation of rat livers in UW solution for as few as 4 h led to a significant loss of hepatocyte viability on re-oxygenation (26). In line with these findings, Vreugdenhil et al (27) reported a significant impairment of protein synthesis after 4 h of cold storage.…”
Section: Dutkowski Et Almentioning
confidence: 71%
“…Iron chelators have already been used in a few experimental studies of liver preservation, yielding protective effects and (in other experiments) no effects (29,30), controversial findings that might be the result of the application mode and concentration of the poorly membranepermeable iron chelator deferoxamine (5). CONCLUSION Our results show that during cold incubation in UW solution, liver endothelial cells undergo cold-induced mitochondrial shortening simultaneously with a decrease in mitochondrial membrane potential and finally lose viability through iron-dependent MPT during rewarming.…”
Section: Figure 3 Mitochondrial Morphology In Cultured Liver Endothementioning
confidence: 99%